Peningkatan Kemampuan Memahami Cerpen Menggunakan Model Make a Match Siswa Kelas IX D SMPN 13 Kota Bengkulu - Setiani, Alisha Putri; Kusmiarti, Reni (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2024)
One of the literature lessons that is compulsory material for grade IX Indonesian lessons is short stories. The purpose of this study is to describe the improvement of students' ability to understand short stories with the make a match model. The research method is quantitative description. The subjects of this research were 27 students of class IX D SMPN 13 Bengkulu City. Data collection in this study used test techniques in the form of pre tests and post tests. Data analysis of this research 1) Students are given pre-test questions, 2) Using the make a match model in short story learning 3) Giving students a posttest question. 4) Entering student score data into the data table. 5) Interpreting data 6) Concluding the improvement of short story understanding skills of students in class IX D SMPN 13 Bengkulu City with make a match. The results showed that there was an increase in the ability to understand short stories pre test with an average of 71.5 the average result of the post test increased by 78.3. The average value of pre test to post test increased by 10%. The increase in the ability to understand the intrinsic elements of short stories pre test with an average of 72.6 the average post test results increased by 78.1. The pre test to post test results experienced an increase of 8%. The increase in the ability to understand the structure of short stories pre test with an average of 70.5 the average result of the post test increased by 78.6. The average pre test to post test increased by 11%.